Strategic autonomy of the EU in the light of CSDP and the changing world order - Gyarmati-Szijj, Dóra; Rada, Péter (Észak-magyarországi Stratégiai Füzetek, 2024)
The development of the European Union’s activity as a security actor is closely linked to the need for global capacity for action in this domain, with a clearly “softer” role definition than NATO, which is derived from a collective security concept. The aim of this study is to identify how and under what circumstances the European Union’s self-definition in the field of security and defense policy has evolved, how it has attempted to make the EU be present in the changing world order as an independent actor asserting its strategic autonomy with a specific voice. The paper looks back not only on the development of the EU security and defense policy, but also highlights the two decades of Hungarian operational involvement in it. Our central assumption is that the strengthening of the EU’s strategic autonomy, in which CSDP is one of the core instruments, cannot be avoided amid the challenges of the modern era if the EU wants to preserve its competitiveness and adaptive responsiveness.